2022
DOI: 10.1055/s-0042-1760110
|View full text |Cite
|
Sign up to set email alerts
|

Automated Decellularization of the Rodent Epigastric Free Flap: A Comparison of Sodium Dodecyl Sulfate–Based Protocols

Abstract: Introduction Free tissue transfer to cover complex wounds with exposed critical structures results in donor-site morbidity. Perfusion decellularization and recellularization of vascularized composite tissues is an active area of research to fabricate complex constructs without a donor site. Sodium dodecyl sulfate (SDS)-based protocols remain the predominant choice for decellularization despite the deleterious effects on tissue ultrastructure and capillary networks. We aimed to develop an automated decellulariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, excessively large, and heavy chambers can restrict the movements of the animal and prevent housing of multiple animals in 1 cage, which further increases distress on the animal and overall cost of the experiment for longer durations of follow-up. 3D printing is an advancing modality, which is becoming more accessible in different aspects of research in regenerative medicine and reconstructive surgery 27,35 . The wound frame described in the current study offers benefits over previously described studies to allow for future reproducible and affordable experiments across various aspects of wound healing research (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, excessively large, and heavy chambers can restrict the movements of the animal and prevent housing of multiple animals in 1 cage, which further increases distress on the animal and overall cost of the experiment for longer durations of follow-up. 3D printing is an advancing modality, which is becoming more accessible in different aspects of research in regenerative medicine and reconstructive surgery 27,35 . The wound frame described in the current study offers benefits over previously described studies to allow for future reproducible and affordable experiments across various aspects of wound healing research (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3D printing is an advancing modality, which is becoming more accessible in different aspects of research in regenerative medicine and reconstructive surgery. 27,35 The wound frame described in the current study offers benefits over previously described studies to allow for future reproducible and affordable experiments across various aspects of wound healing research (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perfusion decellularization technique has been shown to be applicable to a number of different organs and tissues, including those used for reconstructive surgery [15,16]. A limited number of studies reported the decellularization of fasciocutaneous flaps from small [17][18][19][20] and large animals [21,22]. These studies have shown success in the removal of the cells using histological staining and/or the quantification of DNA content, and a few investigated the scaffold further for ECM characterization and biocompatibility [21].…”
Section: Introductionmentioning
confidence: 99%